Methods for Analysing Accounts Receivable and Accounts Payable on Lease Payments - Irina N. Dmitrieva (Ural State University of Economics, 2018)
The article analyses accounts receivable and accounts payable on lease payments. The analysis includes calculating and assessing the share of debt in the balance sheet total and its changes over time; determining profitability and turnover of receivables and payables. When examining the structure and dynamics of debt, the author proposes to arrange data in the form of tables that allow performing calculation and assessment. To form the indicator of debt profitability on lease payments, we apply the method of proportional-value division of the degree of resources (capital) participation in profit, which allows establishing the profitability of specific assets and their sources. In the process of determining the period of receivables turnover by the lessor, we propose to use the amount of received lease payments as turnover. In the process of determining the period of payables turnover by the lessee, we propose to use the amount of repaid lease payments as turnover. Thus, the methods offered in the paper for analysing debt on lease payments allow conducting an integrated assessment of leasing operations efficiency.